Sequential therapy with ranibizumab and dexamethasone intravitreal implant is better than dexamethasone monotherapy for macular oedema due to retinal vein occlusion - Iu, L; Zhao, P; Yeung, I; Fung, N; Lee, J; Wong, R; Chong, V; Wong, I (BMJ Publishing Group, 2014)
Purpose To evaluate the efficacy and safety of sequential therapy with ranibizumab followed by dexamethasone intravitreal implant compared with dexamethasone monotherapy for macular oedema (MO) secondary to retinal vein occlusion (RVO). Methods In this retrospective interventional study, the medical records of subjects with MO due to RVO who received either ranibizumab followed by dexamethasone intravitreal implant (Group 1) or dexamethasone-implant monotherapy (Group 2) were included. Primary outcome was the proportion of subjects who exhibited best-corrected visual acuity (VA) gain and resolution of MO within 6 months. Results Thirty-three eyes were included (17 in Group 1, 16 in Group 2). More subjects in Group 1 exhibited a VA gain of at least 0.5 (LogMAR units hereafter) than Group 2 (29% vs 0%, p=0.044). The speed of VA gain was greater in Group 1 (1.4±0.8 months vs 2.7±1.4 months, p=0.020). MO was controlled in more subjects in Group 1 at all measured time intervals, and this difference was statistically significant at 3 months and 4 months. Subjects with branch RVO experienced VA gain more rapidly if they were from Group 1 (p=0.023). Conclusions Sequential therapy was found to be more effective than dexamethasone monotherapy in treating MO due to RVO. © 2014 by the BMJ Publishing Group Ltd.